SISTEM PENCAHAYAAN DENGAN FUZZY LOGIC CONTROLLER - Arif Basuki; Sugiarto Kadiman; Rizki Ismail (KURVATEK, 2021)
A “newest” room lighting system always links with environmental issues for reducing the consumption of primary energy such as coal and oil. The process carry out by adding natural lighting as solar lighting into artificial lighting. But the problem in combining these systems depends significantly on the condition of natural lighting, such as on weather conditions and light interference based on building construction (isolated or not isolated). Smart systems such as fuzzy logic can be used solution the problem. From the results of this study is artificial lighting can be reduced by half from its maximum condition but with different error margins depending on amount of light interference obtained. The values of these results can be monitored in real-time with IoT (Internet of Thing) media. Keywords: “The newest” lighting systems, Artificial and natural hybrid system, Fuzzy logic controller, monitoring error margin, IoT monitoring